Pemanfaatan Sampah Organik dalam Produksi Pupuk Bokashi di Gabungan Kelompok Tani Rinjani Kecamatan Singaran Pati Kota Bengkulu - Evi Andriani; Jusuf Wahyudi; Lena Elfianty; Lina Widawati (Universitas Prof. Dr. Hazairin, SH, 2021)
The Use of Organic Waste in Bokashi Fertilizer Production at Farmers' Group Association of Rinjani in Singaran Pati District, Bengkulu City The continuous use of inorganic fertilizers by farmers results in disturbed soil fertility and nutrient deficiencies. So far, farmers' group association of Rinjani has also used inorganic fertilizers, which are quite expensive. Therefore, the purpose of this community service was to educate farmers on the farmers' group association of Rinjani on how to utilize organic waste from the surrounding environment to be processed into bokashi fertilizer. The ingredients used were leftover vegetables, fruits and dried leave. The Effective Microorganism 4 (EM4) was used as decomposer to speed up the composting process. The process of making bokashi fertilizer from vegetable and fruit waste was running smoothly. The bokashi obtained was very good. This was indicated by the characteristic of blackish brown color, crumb texture and has an odor like the smell of earth in general.